2020
DOI: 10.1093/jn/nxaa044
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing the Ratio of Dietary Linoleic to α-Linolenic Acid from 10 to 4 by Changing Only the Former Does Not Prevent Adiposity or Bone Deterioration in Obese Mice

Abstract: Background Linoleic acid (LA; 18:2n–6) has been considered to promote low-grade chronic inflammation and adiposity. Studies show adiposity and inflammation are inversely associated with bone mass. Objectives This study tested the hypothesis that decreasing the dietary ratio of LA to α-linolenic acid (ALA, 18:3n–3), while keeping ALA constant, mitigates high-fat diet (HF)-induced adiposity and bone loss. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…We identified 5193 records in the initial search and then removed 1930 duplicates. After the screening based on titles, abstracts, and full‐texts, 80 articles 16,19–97 were finally included in systematic review and 60 articles 16,19–24,26,27,29–38,40–42,44–46,48,50–53,55,56,59,60,64,66,68,70–74,76–79,81–84,86,88–90,92–97 with data of μCT or bone mechanical properties assessment were included in the meta‐analysis (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified 5193 records in the initial search and then removed 1930 duplicates. After the screening based on titles, abstracts, and full‐texts, 80 articles 16,19–97 were finally included in systematic review and 60 articles 16,19–24,26,27,29–38,40–42,44–46,48,50–53,55,56,59,60,64,66,68,70–74,76–79,81–84,86,88–90,92–97 with data of μCT or bone mechanical properties assessment were included in the meta‐analysis (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…We identified 5193 records in the initial search and then removed 1930 duplicates. After the screening based on titles, abstracts, and full-texts, 80 articles 16, were finally included in systematic review and 60 articles 16,[19][20][21][22][23][24]26,27,[29][30][31][32][33][34][35][36][37][38][40][41][42][44][45][46]48,[50][51][52][53]55,56,59,60,64,66,68,[70][71][72][73][74][76][77][78][79][81][82][83][84]…”
Section: Search Resultsmentioning
confidence: 99%
“…Most linseed oils are processed either for nutritive uses or industrial purposes depending on the fatty acid profile of the oil. The modification of fatty acid profile (such as linolenic acid, linoleic acid, and the ratio of linoleic to linolenic acid) to improve oil quality is an important and evolving theme in linseed research to meet nutritional needs and industrial criteria in the modern market (Cao et al, 2020; Ceh et al, 2020). Overall, families #84, 23, 95, 11, 1, 96, 31, 51, 70, 71, 76, 74, 48, 59, 89, 16, 30, 61، 3، 24, 22, 94, 45، 103، 90, 13, 15, and 7 had above average values for seed yield and oil content and possessed advantage for these traits.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we found that S. mukorossi seed oil significantly increased mineralized nodules of WJMSCs ( Figure 3 ). As mentioned above, ω-3 UFAs significantly increase bone regeneration [ 7 , 9 , 10 , 32 ] and can promote bone regeneration by enhancing calcium ion transmission [ 33 ] and strengthening at the Akt signaling pathway for cell membranes [ 34 ]. However, ω-6 UFAs can activate osteoclasts [ 15 ], and several studies have indicated that the ratio of ω-3 to ω-6 UFAs within cell membranes can be an indicator of cellular function [ 11 ], particularly in bone regeneration pathways induced by cell membranes [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, recent research has found that the effects of ω-3 and ω-6 UFA on bone health are different. Some studies suggest that ω-3 UFA, such as docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA), significantly increase bone regeneration and improve microstructure and structural strength [ 7 , 8 , 9 , 10 ]. Additionally, animal studies have shown that ω-3 UFA not only has anti-inflammatory effects [ 11 ] but also reduced osteoclasts by 60% and bone resorption by 80% [ 12 ].…”
Section: Introductionmentioning
confidence: 99%